'Extreme Mass Spectrometry': the role of mass spectrometry in the study of the Antarctic Environmentm. (January 2015) - Banoub, J.; Delmas, G.-H.; Joly, N.; Mackenzie, G.; Cachet, N.; Benjelloun‐Mlayah, B.; Delmas, M.
<x xml:space="preserve">Abstract</x> Lignin is a complex biopolymer composed of aromatic alcohols known as monolignols. It is most commonly derived from wood, and is an integral part of the secondary cell walls of plants. As a biopolymer, lignin is unusual because of its heterogeneity and lack of a defined primary structure. The chemical structural analysis of the lignin polymer is mostly performed by destructive analysis methods. In these methods, the isolated lignin is depolymerized to produce small fragments that provide partial structural information of the original native structure. The large variation in size and molecular diversity of lignin makes its analysis one of the last frontiers for mass spectrometry. In this special feature article, Joseph Banoub and co‐workers critically describe the different mass spectrometry approaches that have been used to characterize lignin with a special emphasis on modern soft ionization methods. Pr. Banoub is principal research scientist at Fisheries and Oceans Canada and adjunct faculty member at the Memorial University of Newfoundland, St John's, NL, Canada. His present research interests include tandem mass spectrometry of biologically active molecules. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>